Effectiveness of Nearpod-Based Interactive Learning Media in Enhancing Students’ Scientific Literacy and Numeracy in Renewable Energy Topic - Ellianawati, Ellianawati; Sipayung, Elisabeth Sabrina Purnama Sari; Subali, Bambang; Linuwih, Suharto; Simbulas, Lolly Jean (FKIP Universitas Lampung, 2025)
The inadequate science literacy and numeracy levels of class X students in the 2021/2022 academic year at SMA Negeri 1 Ajibarang in physics learning, particularly in the domain of renewable energy materials, can be attributed to the limited engagement of science literacy and numeracy in the available learning media. The internet's potential as a learning tool has not been maximally utilized, resulting in a suboptimal learning experience for Generation Z students. In addition, some digital platforms commonly used by teachers are still not optimal in accommodating learning due to several weaknesses, such as limited material and interactive features, as well as information that is prone to being missed during the online discussion process through chat. These problems can be solved by utilizing Nearpod-based interactive learning media. This study aims to analyze the effectiveness of the media and compare which media exploration is considered most effective in enhancing students' science literacy and numeracy. The study employed a pre-experimental approach, utilizing a pre-test and post-test design with three experimental groups. The results indicated that experimental groups A, B, and C enhanced science literacy and numeracy. The N-gain scores of these groups were classified as 'low', with N-gain scores of 0.15, 0.13, and 0.07, respectively, for experimental groups A, B, and C regarding science literacy. The numeracy literacy of experimental groups A, B, and C were 0.20, 0.18, and 0.01, respectively. The conclusion drawn from these data is that Nearpod media is effective in enhancing science literacy and numeracy in the context of renewable energy, especially in the explanation of scientific phenomena in science literacy and the utilization of concepts, facts, procedures, and reasoning in mathematics in numeracy literacy. The utilization of Nearpod in blended learning is more efficacious than its use in flipped learning and print, with an N-gain value of science literacy and numeracy. Keywords: nearpod, science literacy skills, physics numeracy literacy, renewable energy.